Peripheral neuropathies, B vitam Vitamins B1, B6, and B12 and Peripheral Neuropathies: A Systematic Review of the Literature.: Vitaminas B1, B6, B12 y Neuropatías Periféricas. Revisión sistemática de la literatura. | 周围神经病、维生素B1、B6和B12：文献系统综述 - Longa López, John (2024)
The term peripheral neuropathy includes very varied and complex conditions that present difficulties in their diagnostic and therapeutic approach. One of the factors underlying these entities is the deficiency of neurotrophic vitamins B1, B6 and B12. Given the uncertainity and poorly known extremes of this subject and the empirical approach when using the therapeutic resources, a systematic search of the literature has been carried out trying to organize and base on scientific evidence the ideas and conflicting points that have presided over the approach to the issue by the professionals concerned by it. This study serves as the basis for an attempt at expert consensus that promotes a series of recommendations that rationalize and facilitate the management of the issue in clinical practice.